NF-κB–inducing kinase plays an essential T cell–intrinsic role in graft-versus-host disease and lethal autoimmunity in mice - Murray, Susan E. (American Society for Clinical Investigation, 2011)
NF-κB–inducing kinase (NIK) is an essential upstream kinase in noncanonical NF-κB signaling. NIK-dependent NF-κB activation downstream of several TNF receptor family members mediates lymphoid organ development and B cell homeostasis. Peripheral T cell populations are normal in the absence of NIK, but the role of NIK during in vivo T cell responses to antigen has been obscured by other developmental defects in NIK-deficient mice. Here, we have identified a T cell–intrinsic requirement for NIK in graft-versus-host disease (GVHD), wherein NIK-deficient mouse T cells transferred into MHC class II mismatched recipients failed to cause GVHD. Although NIK was not necessary for antigen receptor signaling, it was absolutely required for costimulation through the TNF receptor family member OX40 (also known as CD134). When we conditionally overexpressed NIK in T cells, mice suffered rapid and fatal autoimmunity characterized by hyperactive effector T cells and poorly suppressive Foxp3(+) Tregs. Together, these data illuminate a critical T cell–intrinsic role for NIK during immune responses and suggest that its tight regulation is critical for avoiding autoimmunity.